Vibrio vulnificus Has the Transmembrane Transcription Activator ToxRS Stimulating the Expression of the Hemolysin Gene vvhA - Lee, Shee Eun (American Society for Microbiology, 2000)
In an attempt to dissect the virulence regulatory mechanism in Vibrio vulnificus, we tried to identify the V. cholerae transmembrane virulence regulator toxRS (toxRS(Vc)) homologs in V. vulnificus. By comparing the sequences of toxRS of V. cholerae and V. parahaemolyticus (toxRS(Vp)), we designed a degenerate primer set targeting well-conserved sequences. Using the PCR product as an authentic probe for Southern blot hybridization, a 1.6-kb BglII-HindIII fragment and a 1.2-kb HindIII fragment containing two complete open reading frames and one partial open reading frame attributable to toxR(Vv), toxS(Vv), and htpG(Vv) were cloned. ToxR(Vv) shared 55.0 and 63.0% sequence homology with ToxR(Vc) and ToxR(Vp), respectively. ToxS(Vv) was 71.5 and 65.7% homologous to ToxS(Vc) and ToxS(Vp), respectively. The amino acid sequences of ToxRS(Vv) showed transmembrane and activity domains similar to those observed in ToxRS(Vc) and ToxRS(Vp). Western blot analysis proved the expression of ToxR(Vv) in V. vulnificus. ToxRS(Vv) enhanced, in an Escherichia coli background, the expression of the V. vulnificus hemolysin gene (vvhA) fivefold. ToxRS(Vv) also activated the ToxR(Vc)-regulated ctx promoter incorporated into an E. coli chromosome. A toxR(Vv) null mutation decreased hemolysin production. The defect in hemolysin production could be complemented by a plasmid harboring the wild-type gene. The toxR(Vv) mutation also showed a reversed outer membrane protein expression profile in comparison to the isogenic wild-type strain. These results demonstrate that ToxR(Vv) may regulate the virulence expression of V. vulnificus.